The Influence Of School Principals' Academic Supervision On Teacher Learning Performance And Teacher Job Satisfaction - Nor Khofifah; Malida (STIT Syekh Muhammad Nafis Tabalong, 2025)
Improving the quality of education begins with efforts to enhance teachers' teaching performance and job satisfaction. One of the effective approaches is academic supervision conducted by the school principal, which provides guidance and support to help teachers achieve established learning objectives. Effective academic supervision makes teachers feel more valued and supported, thereby increasing their job satisfaction. This study examines the significant influence of the principal's academic supervision on teachers' teaching performance and job satisfaction. It employs a correlational study design with a quantitative approach using survey techniques. Data was collected through a 5-point Likert scale questionnaire distributed to 112 teachers at several high-performing private Madrasah Ibtidaiyah in Hulu Sungai Utara. The data was analyzed using SEM-PLS through SmartPLS 3.0 software. The results reveal that principal's academic supervision at high-performing private Madrasah Ibtidaiyah in Hulu Sungai Utara has very high average scores: 4.35 for teachers' teaching performance and 4.44 for teachers' job satisfaction. Hypothesis testing using SmartPLS indicates a significant influence of the principal's academic supervision on teachers' teaching performance (T-Statistic 30.535 > T-table 1.982, P Value 0.000 < 0.05) and on teachers' job satisfaction (T-Statistic 15.113 > T-table 1.982, P Value 0.000 < 0.05). Simultaneously, the principal's academic supervision significantly influences teachers' teaching performance with an R-Square value (R² = 0.775) or 77.5% and teachers' job satisfaction with an R-Square value (R² = 0.615) or 61.5%.